Calcium looping in the steel industry: GHG emissions and energy demand. (May 2023) - Carbone, Claudio; Ferrario, Daniele; Lanzini, Andrea; Verda, Vittorio; Agostini, Alessandro; Stendardo, Stefano
Highlights: Calcium looping (CaL) process is optimized for carbon capture in steel industries. CaL integration into the blast furnace systems can reduce GHG emissions up to 66%. The benefit of CaL integration into direct reduction systems are limited. Trade-offs between GHG emissions reduction and primary energy consumption are shown. Timeframe of the GHG metric used (20 or 100 y) significantly impacts the outcome. Abstract: The development of innovative solutions to decarbonize hard-to-abate sectors is a priority challenge in the quest to mitigate climate change. The GHG emission mitigation potential of the carbon capture Calcium Looping process (CaL) is investigated in this work. Two steelmaking routes are modeled: a blast furnace and a basic oxygen furnace (BF-BOF), and a direct reduction process and an electric arc furnace (DR-EAF), both of which are coupled with CaL technology. The carbon footprints of the two systems were evaluated, through an eco-design approach, with the aim of quantifying the GHG emissions and identifying the hotspots of the emissions. DR-EAF was found to be characterized by lower GHG emissions than BF-BOF (0.9 t vs 2.1 t CO2 eq per tonne of liquid steel produced), as it is intrinsically more efficient and less carbon intensive. For this reason, the adoption of the CaL technology resulted to be more effective when applied to the BF-BOF, as it led to a reduction in GHG emissions of up to 66%, with respect to baseline plant configuration without the CaL system. The primary energy demand increased considerably by the integration of CaL in BF-BOF and this would be amplified in a future scenario dominated by renewable energy resources. We also remarked the importance of the CaL technology being circular to reduce and reuse the spent material deployed for CO2 sequestration. This work ends with a parametric analysis that points out the importance of the timescale of climate change metrics on the evaluation of the carbon footprint. Graphical abstract: Image, graphical abstract